Convert -35 Fahrenheit to Celsius

What is -35 degrees Fahrenheit in Celsius? Just type in either box, and the number in the other box will be converted automatically.
Fahrenheit
Celsius
-35° Fahrenheit = -37.22° Celsius
(rounded to 4 digits)
How hot is -35 degrees Fahrenheit? How cold? Convert between Fahrenheit and Celsius.
More temperatures starting with -35 degrees in Fahrenheit
Note: results are rounded
-35.00 °F = -37.22 °C -34.75 °F = -37.08 °C -34.50 °F = -36.94 °C -34.25 °F = -36.81 °C
-34.99 °F = -37.22 °C -34.74 °F = -37.08 °C -34.49 °F = -36.94 °C -34.24 °F = -36.80 °C
-34.98 °F = -37.21 °C -34.73 °F = -37.07 °C -34.48 °F = -36.93 °C -34.23 °F = -36.79 °C
-34.97 °F = -37.21 °C -34.72 °F = -37.07 °C -34.47 °F = -36.93 °C -34.22 °F = -36.79 °C
-34.96 °F = -37.20 °C -34.71 °F = -37.06 °C -34.46 °F = -36.92 °C -34.21 °F = -36.78 °C
-34.95 °F = -37.19 °C -34.70 °F = -37.06 °C -34.45 °F = -36.92 °C -34.20 °F = -36.78 °C
-34.94 °F = -37.19 °C -34.69 °F = -37.05 °C -34.44 °F = -36.91 °C -34.19 °F = -36.77 °C
-34.93 °F = -37.18 °C -34.68 °F = -37.04 °C -34.43 °F = -36.91 °C -34.18 °F = -36.77 °C
-34.92 °F = -37.18 °C -34.67 °F = -37.04 °C -34.42 °F = -36.90 °C -34.17 °F = -36.76 °C
-34.91 °F = -37.17 °C -34.66 °F = -37.03 °C -34.41 °F = -36.89 °C -34.16 °F = -36.76 °C
-34.90 °F = -37.17 °C -34.65 °F = -37.03 °C -34.40 °F = -36.89 °C -34.15 °F = -36.75 °C
-34.89 °F = -37.16 °C -34.64 °F = -37.02 °C -34.39 °F = -36.88 °C -34.14 °F = -36.74 °C
-34.88 °F = -37.16 °C -34.63 °F = -37.02 °C -34.38 °F = -36.88 °C -34.13 °F = -36.74 °C
-34.87 °F = -37.15 °C -34.62 °F = -37.01 °C -34.37 °F = -36.87 °C -34.12 °F = -36.73 °C
-34.86 °F = -37.14 °C -34.61 °F = -37.01 °C -34.36 °F = -36.87 °C -34.11 °F = -36.73 °C
-34.85 °F = -37.14 °C -34.60 °F = -37.00 °C -34.35 °F = -36.86 °C -34.10 °F = -36.72 °C
-34.84 °F = -37.13 °C -34.59 °F = -36.99 °C -34.34 °F = -36.86 °C -34.09 °F = -36.72 °C
-34.83 °F = -37.13 °C -34.58 °F = -36.99 °C -34.33 °F = -36.85 °C -34.08 °F = -36.71 °C
-34.82 °F = -37.12 °C -34.57 °F = -36.98 °C -34.32 °F = -36.84 °C -34.07 °F = -36.71 °C
-34.81 °F = -37.12 °C -34.56 °F = -36.98 °C -34.31 °F = -36.84 °C -34.06 °F = -36.70 °C
-34.80 °F = -37.11 °C -34.55 °F = -36.97 °C -34.30 °F = -36.83 °C -34.05 °F = -36.69 °C
-34.79 °F = -37.11 °C -34.54 °F = -36.97 °C -34.29 °F = -36.83 °C -34.04 °F = -36.69 °C
-34.78 °F = -37.10 °C -34.53 °F = -36.96 °C -34.28 °F = -36.82 °C -34.03 °F = -36.68 °C
-34.77 °F = -37.09 °C -34.52 °F = -36.96 °C -34.27 °F = -36.82 °C -34.02 °F = -36.68 °C
-34.76 °F = -37.09 °C -34.51 °F = -36.95 °C -34.26 °F = -36.81 °C -34.01 °F = -36.67 °C